Access to HPV vaccination for boys in the United Kingdom. Issue 1 (September 2018) - Prue, Gillian; Grimes, David; Baker, Peter; Lawler, Mark
Human papillomavirus (HPV) is a common sexually transmitted infection. There is a well-established link between HPV and the development of cervical cancer, but HPV infection is also associated with vaginal and vulvar cancer, head and neck cancers as well as anal cancers in both sexes and penile cancer in men. Despite this, since its introduction in 2008, the United Kingdom has included only girls in its vaccination programme and, in 2017, suggested that it was not cost effective to extend the vaccine to adolescent boys. Men-who-have-sex-with-men (MSM) have been offered the HPV vaccine in the United Kingdom since 2016. A number of countries (21 to date) have implemented a universal HPV vaccination programme, with many countries arguing that female-only vaccination programmes protect males via herd immunity and that MSM will be protected via targeted vaccination programmes, although these may be limited in their effectiveness. Following an advocacy campaign to extend the HPV vaccination programme to boys in the United Kingdom, in July 2018 the Joint Commission for Vaccination and Immunisation recommended that boys should be included alongside 12/13-year-old girls in a school-based programme. Given that this decision has been delayed by many years, it is imperative that the UK Government and Department of Health implement this vaccine programme as quickly as possible and by September 2019 at the latest, that a catch-up programme for boys is introduced and, given the feminisation of HPV, that information materials on HPV vaccination that are targeted at boys, their parents and teachers are made widely available.